IDENTIFIKASI ORIENTASI REKAHAN MIKRO AREA PANAS BUMI MONTE AMIATA BERDASARKAN ANALISIS STUDI SHEAR WAVE SPLITTING - Irfan - Hanif; Ahmad Zaenudin; Nandi Haerudin; Rahmat C Wibowo (Universitas Mataram, 2020)
Shear Wave Splitting is an application of seismic wave to analyse the anisotropy level of a certain medium. Generally, shear wave propagation through a rock formation will be polarized (φ) into two parts especially when the medium structures are different, such as fracture. The polarized shear wave which is perpendicular to fracture will propagate slower than the wave that propagates parallel to the fracture. The delay time (δt) of both wave is proportional with the fracture intensity along the wave propagation from the source to the station. The description regarding fracture orientation can be obtained by analysing both Shear Wave Splitting parameters (φ and δt), and this information is adequately important in geothermal exploration or exploitation phase at Mt. Amiata. Based on the result of this research, the micro earthquake source is focused on the east to the south area and spread along 3 earthquake stations. The existence of micro earthquake source is mainly focused at the depth of 1 to 4 km. In addition, the polarization direction of each earthquake station at the geological map shows a dominant fracture orientation consistently at NW-SE. All of the three stations also show that the polarization direction is integrated to the local fault existence in the subsurface. Furthermore, the research shows that the high intensity fracture distribution occurred at MCIV station area in the southern part of research location. Meanwhile, the low intensity fracture distribution occurred at ARCI and SACS station area in the western and the eastern part of research location. The high value of fracture intensity accompanied by the high amount of structure intensity, strengthen the prediction of the high anisotropy existence which potentially tends to the high permeability presence at the area.Keywords: shear wave splitting, anisotropy, fracture, geothermal, polarization direction, fracture intensity.